Pemanfaatan Multimedia Presentasi Dan Media Cetak Dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Hindu - I Wayan Sirna; Putu Ersa Rahayu Dewi (Jurnal Penjaminan Mutu, 2018)
Education is the human necessity and it has major role to gain better life. The education quality depends on the government policy, the societies’ role, and schools’ efforts to due education. The school is one of the institution that enrolls teaching and learning activity and it needs some components to support its activity. The achievement of educational quality can be seen on the students’ progress during teaching and learning process. The students’ achievement of Hinduism lesson is quite low caused they had nothing from the subjects that being learned. The Hinduism lesson students’ achievement using printed media and multimedia presentation due through classroom management, teaching materials, develop students’ learning activity, the assessment of teaching and learning process, and the assessment of comprehending concept/ knowledge, these results raise 20% from the former results.